How does brand image moderate the factors influencing purchase intention? - Maretta Ginting; Ronnie Togar Mulias Sirait; Wan Suryani (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
This study examines the moderating role of brand image in the relationship between influencers, loyalty, price, and influencer marketing on purchasing decisions. Using a survey of 103 online shoppers and the robust least squares model, the findings indicate that brand image, price, and consumer reviews generally have a positive impact on purchasing decisions, while influencer marketing and loyalty are not significant factors. Furthermore, brand image negatively moderates the effects of price and consumer reviews. This suggests that although lower prices encourage purchases, a strong brand image can reduce consumers' price sensitivity. Similarly, consumers may rely more on brand image than on consumer reviews when forming purchase intentions. These findings highlight the critical role of brand image in purchasing decisions, as it can make products less sensitive to both price and negative consumer reviews.